Third Asia-Pacific consensus recommendations on colorectal cancer screening and postpolypectomy surveillance. Issue 11 (24th August 2022) - Sung, Joseph J Y; Chiu, Han-Mo; Lieberman, David; Kuipers, Ernst J; Rutter, Matthew D; Macrae, Finlay; Yeoh, Khay-Guan; Ang, Tiing Leong; Chong, Vui Heng; John, Sneha; Li, Jingnan; Wu, Kaichun; et al.
Abstract : The Asia-Pacific region has the largest number of cases of colorectal cancer (CRC) and one of the highest levels of mortality due to this condition in the world. Since the publishing of two consensus recommendations in 2008 and 2015, significant advancements have been made in our knowledge of epidemiology, pathology and the natural history of the adenoma-carcinoma progression. Based on the most updated epidemiological and clinical studies in this region, considering literature from international studies, and adopting the modified Delphi process, the Asia-Pacific Working Group on Colorectal Cancer Screening has updated and revised their recommendations on (1) screening methods and preferred strategies; (2) age for starting and terminating screening for CRC; (3) screening for individuals with a family history of CRC or advanced adenoma; (4) surveillance for those with adenomas; (5) screening and surveillance for sessile serrated lesions and (6) quality assurance of screening programmes. Thirteen countries/regions in the Asia-Pacific region were represented in this exercise. International advisors from North America and Europe were invited to participate.